Hadith Ahad and Its Argumentation in the Problem of Faith in the Perspective of Muhammad Al-Ghazali: Hadis Ahad dan Kehujahannya dalam Masalah Aqidah menurut Perspektif Muhammad Al-Ghazali - Adwiah, Amalia Rabiatul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Differences of opinion among the scholars, one of which is Muhammad Al-Ghazali in his control of Sunday hadiths and statements related to Sunday hadiths, should not be relied upon in matters of faith because they are not qat'iyyah al thubut, which raises many doubts, so their validity needs to be studied. This study discusses the blasphemy of ahad hadith from Al-Ghazali's perspective. This research is included in the category of qualitative research that utilizes literature study techniques. Document data comes from library documents, both primary and secondary. This study is expected to be able to provide answers regarding the blasphemy of Sunday hadith against Islamic teachings from the perspective of Muhammad Al-Ghazali. The results of this study show that Al-Ghazali expressed his rejection of the blasphemy of ahad hadith in matters of faith. First, the ahad hadith, even though the sanad is valid, is unable to convey faith and truth but is in the form of assumptions or conjectures. Second, when it comes to the principle of faith, of course everything must be based on strong evidence, not speculation